2020
DOI: 10.3390/biom10060867
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Apoptotic and Antioxidant Effects of 3-Epi-Iso-Seco-Tanapartholide Isolated from Artemisia argyi against Iodixanol-Induced Kidney Epithelial Cell Death

Abstract: Iodixanol is a non-ionic iso-osmolar contrast agent, but it is a risk factor for kidney damage and increases morbidity and mortality. In this study, we investigated the effect of 9 sesquiterpenes isolated from mugwort (Artemisia argyi) in contrast agent-induced cytotoxicity in LLC-PK1 cells. Cells were exposed to nine sesquiterpene compounds for 2 h, followed by incubation with iodixanol for 3 h. Cell viability was assessed using the Ez-Cytox assay. The level of reactive oxygen species was measured using 2′,7′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Alpha diversity, commonly measured in terms of Chao1 richness and Shannon diversity, reflects the microbial abundance and species diversity of a single sample [ 54 ]. As shown in Figure 2 , the alpha diversity was higher in AA than in WS before ensiling.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha diversity, commonly measured in terms of Chao1 richness and Shannon diversity, reflects the microbial abundance and species diversity of a single sample [ 54 ]. As shown in Figure 2 , the alpha diversity was higher in AA than in WS before ensiling.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a G2/M cell cycle arrest coupled with an induction of the S phase fraction, especially in the case of U87MG cells, is known to be associated with the anti-glioma activity of natural compounds such as deglucohellebrin [ 18 ], thereby supporting a similar mechanism of action that may be associated with an anti-inflammatory effect and the action of NF-kB transcription factor. Previous studies have revealed that rupicolin A had a protective effect on iodixanol-induced cytotoxicity in LLC-PK1 cells at concentrations of 10 µM, with a cell survival rate of 75.1 ± 1.9% [ 15 ]. The current research offered evidence that natural substances exert anti-cancer effects, thereby suggesting that rupicolin A and B are promising candidates for further research, given the continuous need for novel therapies for the second cause of human mortality [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other examples refer to ligustolide-A and arteludovicinolide-A that exhibit anti-inflammatory properties or 1α,6α,8α-trihydroxy-5α,7β H-guaia-3,10,14,11,13-trien-12-oic acid and 1α,6α,8α-trihydroxy-5α,7βH-guaia-3,9,11,13-trien-12-oic acid, which may significantly enhance the proliferation of beneficial macrophages [ 14 ]. Moreover, in a recent study, the protective effect of rupicolin A and acrifolide has been investigated against iodixanol-induced cytotoxicity in cultured renal tubular cells (LLC-PK1), although none of them showed any toxic effect at 25μΜ and 50μΜ, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that it possesses antioxidant, anti-cancer, anti-inflammatory, immunomodulatory, as well as antimicrobial properties Abbreviations: AAEO, Artemisia argyi essential oil; DMEM, Dulbecco's Modified Eagle Medium; EMT, epithelial-mesenchymal transition; HCC, hepatocellular carcinoma; H&E, hematoxylin and eosin staining; MTT, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; PBS, phosphate buffered saline; RT-qPCR, real-time quantitative PCR. (Li et al, 2018;Lee et al, 2020). A wide range of phytochemicals including essential oils, flavonoids, organic acids, terpenes, polysaccharides, and coumarins have been identified in Artemisia argyi (Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…is a famous plant species in traditional Chinese medicine used to control dysmenorrhea, abdominal pain, and inflammation ( Editorial Board of Chinese Pharmacopoeia, 2015 ). Recent studies have shown that it possesses antioxidant, anti-cancer, anti-inflammatory, immunomodulatory, as well as antimicrobial properties ( Li et al, 2018 ; Lee et al, 2020 ). A wide range of phytochemicals including essential oils, flavonoids, organic acids, terpenes, polysaccharides, and coumarins have been identified in Artemisia argyi ( Song et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%